Revisiting the Multicultural Experience-creativity Link: The Effects of Cultural Distance and Comparison Mindset - CHENG, Chi-Ying (Institutional Knowledge at Singapore Management University, 2013)
A growing literature provides evidence for the multicultural experience-creativity link such that exposure to the juxtaposition of two cultures facilitates individual creativity. The underlying mechanisms for this relationship, however, are still far from being well explored. Drawing upon the novel perspective of motivated cognition, we hypothesize that two factors interact to affect creative outcomes: (a) perceived cultural distance between the two juxtaposed cultures, and (b) comparison mind-sets. Specifically, we argue that individuals’ creative performance will be increased only when a difference mind-set is employed to process the cultural stimuli that are sufficiently different from each other. In two studies, individuals exposed to dual cultural primes with higher levels of perceived cultural distance consistently performed more adeptly in creative insight tasks when they personally predisposed to or experimentally manipulated to adopt a difference (vs. similarity) mind-set. Theoretical and practical implications are discussed.